Neutron and photon out-of-field doses at cardiac implantable electronic device (CIED) depths. (October 2021) - Aslian, Hossein; Severgnini, Mara; Khaledi, Navid; Ren Kaiser, Stefano; Delana, Anna; Vidimari, Rossella; de Denaro, Mario; Longo, Francesco
Abstract: The accuracy of an out-of-field dose from an Elekta Synergy accelerator calculated using the X-ray Voxel Monte Carlo (XVMC) dose algorithm in the Monaco treatment planning system (TPS) for both low-energy (6 MV) and high-energy (15 MV) photons at cardiac implantable electronic device (CIED) depths was investigated through a comparison between MCNPX simulated out-of-field doses and measured out-of-field doses using three high spatial and sensitive active detectors. In addition, total neutron equivalent dose and fluence at CIED depths of a 15-MV dose from an Elekta Synergy accelerator were calculated, and the corresponding CIED relative neutron damage was quantified. The results showed that for 6-MV photons, the XVMC dose algorithm in Monaco underestimated out-of-field doses in all off-axis distances (average errors: −17% at distances X < 10 cm from the field edge and −31% at distances between 10 < X ≤ 16 cm from the field edge), with an increasing magnitude of underestimation for high-energy (15 MV) photons (up to 11%). According to the results, an out-of-field photon dose at a shallower CIED depth of 1 cm was associated with greater statistical uncertainty in the dose estimate compared to a CIED depth of 2 cm and clinical depth of 10 cm. Our results showed that the relative neutron damage at a CIED depth range for 15 MV photon is 36% less than that reported for 18 MV photon in the literature. Highlights: A MC model of the Elekta Synergy head to assess out-of-field doses for both low and high energy photons. The accuracy of out-of-field dose calculations by XVMC dose algorithm in Monaco. An out-of-field dose analysis of microdiamond, PinPoint 3D, Semiflex 3D. Neutron equivalent dose and fluence at CIED depths. The CIED relative neutron damage of a 15 MV photon beam was quantified.